On the boundedness of the total variation of the logarithm of a Blaschke product - Kondratyuk, Ya. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We establish that, for a Blaschke product B(z) convergent in the unit disk, the condition - ∞